Personnel Management : Management of Hunam Resoruces - Mamoria C B (Mumbai Himalaya Publishing, 1984)
Master : 230
Keywords: Mamoria C.B.,Personnel Management : Managem,Psychological Testing,Motivation,Leadership,Wage & Salary,Performance Appraisal